(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article discusses the need to ensure interdisciplinary integration to ensure the effectiveness of teaching history in secondary schools. At the same time, the need to ensure interdisciplinary integration is scientifically substantiated using various examples.